Service Learning and Early Childhood Education: Intersection of Developmentally Appropriate Practice and P.A.R.E. Issue 2 (2nd April 2020) - Baumgartner, Jennifer; DiCarlo, Cynthia; Casbergue, Renée
ABSTRACT: Service learning (SL) is both a pedagogy and philosophy adopted by many early childhood teacher educators. Extant research suggests the incorporation of service-learning can be effective for facilitating preservice teacher learning of curriculum, pedagogy, approaches to diverse learners and families as well as establishing a professional identity. To guide the intentional adoption of SL and its assessment in early childhood teacher education programs, the authors present the Developmentally Appropriate Practice /P.A.R.E. model and illustrate how the model might be applied in a teacher education program. Challenges to incorporating service-learning in early childhood education programs and future areas of research are described.